Mixing characteristics of the Athabasca River below Fort McMurray – Winter Conditions ... - Beltaos, S. (University of Alberta Library, 1979)
This report presents the results of a comprehensive assessment of mixing characteristics of the Athabasca River below Fort McMurray under ice-covered flow conditions. A brief review of mixing processes in natural streams is followed by a description of two tracer tests conducted in February 1978 to provide the necessary field documentation of the Athabasca River. The results of these tests are analysed using recent theoretical models available in the literature. An average value for the transverse mixing coefficient is determined from the results of the first test which was a steady state test. This coefficient compares favourably with that found from a preliminary test in 1974 under similar flow conditions. The results of the second test, which involved central injection of a slug, are compared with a one dimensional model developed earlier by the author. This model is shown to give fair predictions beyond 20 km from the injection site. It is suggested that this limiting distance be increased to about 80 km ...